2016
DOI: 10.1210/en.2016-1085
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Localized Estrogen Receptor 1 Is Required for Normal Male Reproductive Development and Function in Mice

Abstract: Estrogen receptor 1 (ESR1) mediates major reproductive functions of 17β-estradiol (E2). Male Esr1 knockout (Esr1KO) mice are infertile due to efferent ductule and epididymal abnormalities. The majority of ESR1 is nuclear/cytoplasmic; however, a small fraction is palmitoylated at cysteine 451 in mice and localized to cell membranes, in which it mediates rapid E2 actions. This study used an Esr1 knock-in mouse containing an altered palmitoylation site (C451A) in ESR1 that prevented cell membrane localization, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 47 publications
8
39
0
Order By: Relevance
“…Those of the cryptorchid bucks expressed stronger staining than those of the normal bucks. These findings demonstrate that estrogen receptors are present in the testes of goats and the stronger staining of Leydig cells in the scrotal testes of unilateral cryptorchid bucks is most probably an indication of improved testosterone metabolism as estrogen receptor has been demonstrated as a major regulator of 17B estradiol effects on reproduction (Nanjappa et al, 2016). This may provide an explanation for the normal histology of germ cells in the scrotal testes of cryptorchid bucks as reported in the present study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Those of the cryptorchid bucks expressed stronger staining than those of the normal bucks. These findings demonstrate that estrogen receptors are present in the testes of goats and the stronger staining of Leydig cells in the scrotal testes of unilateral cryptorchid bucks is most probably an indication of improved testosterone metabolism as estrogen receptor has been demonstrated as a major regulator of 17B estradiol effects on reproduction (Nanjappa et al, 2016). This may provide an explanation for the normal histology of germ cells in the scrotal testes of cryptorchid bucks as reported in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Similar expression of VEGF immunoreactivity has been reported in Yak unilateral cryptorchidism (Chen et al, 2015) Identification of the sites of expression of estrogen is vital, as estrogen has been demonstrated to fascilitate spermatogenesis and other testicular functions (Nanjappa et al, 2016). A slight difference in the staining intensity was observed between Leydig cells from the testes of normal bucks and those of the scrotal testes of the cryptorchid bucks.…”
Section: Discussionsupporting
confidence: 72%
“…Different expression patterns and functions of Cyp19a1b in fish reflect the functional diversity of orthologous genes. It was also surprising to note that the aromatase deficient XY tilapia did not show histopathological phenotypes that were similar to the aromatase deficient XY mouse (Robertson et al, ), while they did have similarity with ERα knockout mice (Hess et al, ; Nanjappa et al, ). Testicular degeneration in the Cyp19a1 knockout male began with ageing and was independent of the efferent duct abnormalities (Robertson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This observation implied that mammalian testes could synthesize estrogen and that the estrogen may contribute to their reproductive function. Blocking estrogen caused damage to the fertility of male mice (Fisher, Graves, Parlow, & Simpson, 1998;Hess et al, 1997;Nanjappa et al, 2016;Oliveira et al, 2002;Robertson et al, 1999;Robertson, Simpson, Lacham-Kaplan, & Jones, 2001). Altogether, compelling evidence has shown that estrogen is involved in regulating mammalian male reproductive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Efferent ductules and epididymal functions are dependent on estrogen signaling through ERα, whose loss impaired ion transport and water re‐absorption, resulting in abnormal sperm (Hess et al, ). Furthermore, a recent study has suggested a new role for the membrane ERα (mERα) in normal sperm development, showing impaired sperm morphology, viability and motility, together with histological alterations of testis, rete testis and ductuli efferentes, in transgenic male mice lacking mERα (Nanjappa et al, ). Concerning ERβ, despite its expression in nearly every cell type of ductuli efferentes and epididymis, a defining role for this estrogen receptor remains unknown in this context (Nie et al, ; Zhou et al, ; Schön et al, ).…”
Section: Discussionmentioning
confidence: 99%